IOM Smart Health Line: Giving back - Vaidya, Pradeep (Journal of Institute of Medicine Nepal, 2011)
DOI: http://dx.doi.org/10.3126/joim.v32i3.4951 Journal of Institute of Medicine, December, 2010; 32:3 1